(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The sitting height ratio is an essential criterion in the diagnosis of growth problems and excessive growth. For the purpose of evaluating the wrestlers’ performance, the investigator compared the differences in body proportionality ‘sitting height-stature index’ between Greco roman and freestyle male wrestlers of 130 kg., and 125 kg. weight category. The researcher has selected ten top-ranked wrestlers of each weight category (Greco roman 130 kg and freestyle 125 kg) from the All India intervarsity championship 2020-21, that competition was organized at Ch. Bansilal University Bhiwani, Haryana on 7/03/2022 to 10/03/2022. We found that a significant difference is existing in the Greco-Roman and freestyle wrestler’s mean Sitting Height-Stature Index of two (130 and 125 kg.) weight categories.